การออกแบบและสร้างเครื่องกำเนิดแรงดันอิมพัลส์แบบพกพาได้ ขนาด 800 V - ชนันนัทธ์ หมู่สุวรรณ (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
To propose a design and construction of a 800 V portable impulse generator. The component value of this impulse generator can be adjusted and this generator can generate impulse waves every 40 ms. The portable impulse generator is constructed for the studying of properties of the impulse voltage wave, especially the 1.2/50 (mu)s lightning impulse waveforms, according to the standard of IEC 60-1. The studies of impulse waveforms are useful for designing of a high voltage equipment.